Digital Marketing at NorthCap University: A Case Study - Nayyar, Ruchi (Indian Journal of Computer Science, 2017)
This case study etches out the digital marketing strategies adopted by The NorthCap University during challenging times. The university implemented best practices of online marketing coupled with effective and efficient execution. This case envisages NorthCap’s challenges in building trust in their online audience and the tools chosen to mitigate them. Marketers must think strategically about exploring the power of the internet to understand potential customers, effectively communicating with them, and leveraging digital technology to increase returns. The readers are also challenged to think about solutions to mitigate risks that could arise from strong online presence especially in social networking sites. This case also brings forth the relevance of analytics in identifying useful web data and justifying investments in digital advertising and promotional activities. Lastly, it provides a set-up to a meeting where a choice from among clearly-defined digital marketing options must be made.This case works especially well if readers have some background knowledge about social media, SEO, web analytics, and content marketing. Social media marketing enabled NorthCap University to identify its target audience, in brand building, lead generation, and relationship building. It fostered user participation on social network sites through regular conversations, honoring feedbacks, and maintaining transparency. One practical challenge the university faced in the process was to evaluate whether their social engagement efforts were able to meet the intrinsic motives of the stakeholders. It was crucial to identify the "value of a like" before proceeding to implementing any fan acquisition strategy. In order to combat this challenge, sophisticated analytical tools were utilized to provide key insights about the digital campaigns. Such statistics helped the university to design more focused campaigns targeting specific audiences.